Effectiveness of Lemon Aromatherapy in Reducing Nausea and Vomiting in 1st Trimester Pregnant Women - Skania, Pratiwi Cahya; Ashari, Elva Febri; Rospia, Evi Diliana; Haerunisa, Dinda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Pregnancy is a physiological condition for women, especially for women of childbearing age. Pregnancy lasts for 42 weeks consisting of 3 trimesters, namely trimester I, II, and III. This study aims to reduce nausea and vomiting in pregnant women in the first trimester at the Akmar Jaya Clinic, Serang City. The research method used in this study was a Quasi Experimental study in one group (one group pre-test post-test). The results showed that the majority of nausea and vomiting frequencies before the intervention were 6-10 times, namely 8 people (50%), after the intervention was mild with a frequency of nausea and vomiting 1-3 times, as many as 12 people (75%). Statistically, the p-value was obtained = 0.000 or less than the α value (0.05). The conclusion is that pregnant women in their first trimester can successfully reduce nausea and vomiting by using lemon aromatherapy at the Akmar Jaya Clinic, Serang City in 2004.